Large-Time-Step-Based Ray-Tracing Modeling of Light Delivery in One-Sidedly Cladding-Removed Step-Index Plastic Optical Fiber under Arbitrary Weave Structure - Sun Hee Moon; In Hwan Sul (Advances in Materials Science and Engineering)
An advanced theoretical method to simulate the light delivery in plastic optical fiber is presented. The final objective is to use “light” as a new media for information delivery in wearable computers. A large-time-step-based ray-tracing algorithm, which was improved from our previous research, was used to simulate the light vector movement in a complex weave structure efficiently. NURBS and free-form-deformation-based modeling was used to mimic the arbitrary weave structure. Experimentally, optical fibers were modified to control the direction of light emission. Particularly, half side of a cladding layer in the radial direction was selectively removed to enhance one-sided fabric light scattering. The cladding-removed plastic optical fiber was adopted in a textile weave structure, and its light scattering was measured quantitatively by varying the removal length, fiber curvature, and fabric weave patterns. To show the validity of the proposed simulation technique, twill structures with varying number of cross repeat numbers were used as a testbed. The unit number 2 was found to be the optimal structure for light emission, when a single POF was embedded in the textile. The proposed model showed the similar result with the actual light intensity measurement, with computation time not much than one second.